Remote Natural Language Sampling of Parents and Children With Autism Spectrum Disorder: Role of Activity and Language Level - Butler, Lindsay K.; La Valle, Chelsea; Schwartz, Sophie; Palana, Joseph B.; Liu, Cerelia; Peterman, Natalie; Shen, Lue; Tager-Flusberg, Helen (Frontiers in Communication, 2022)
Natural language sampling (NLS) is a common methodology in research and clinical practice used to evaluate a child's spontaneous spoken language in a naturalistic context. Autism spectrum disorder (ASD) is a complex neurodevelopmental condition that results in heterogeneous language profiles. NLS has emerged as a useful method for better understanding language use and development in this population. Prior work has examined the effects that contexts (e.g., home, lab) and conversational partners (e.g., examiner, parent) have on children’s language production, but less is known about remote collection of interactions between parents and children with ASD at home. Increasing our understanding of in-home remote NLS with children with ASD will improve naturalistic approaches to language assessment in children with ASD. We analyzed natural language samples of 90 dyads of parents and four- to seven-year old children with ASD collected remotely in the home using items and activities from the family's own home. The 15-minute parent-child interactions were transcribed and analyzed for the child's language level measured by the number of different words. We examined the range of activities and the relationship between activities and the child's language level. We found that in-home parent-child activities fell into 13 descriptive categories, but we found no significant difference in child's language level (measured by the mean number of different words) across activities. We found that dyads involving children with higher language levels engaged in significantly fewer different activities compared to children with lower language levels. We found no difference in the number of different words elicited in the five most frequent activities in our sample. These results support the feasibility of remote in-home language sampling. While the types of activities that parent-child dyads engaged in did not affect the richness of language elicited, the number of different activities was associated with the child's language level. Allowing parents to steer children with lower language levels toward more different activities may allow children with lower language to more fully demonstrate their spoken language abilities.